The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1124/dmd.118.084483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Osmolality on the Pharmacokinetic Interaction between Apple Juice and Atenolol in Rats

Abstract: A recent clinical study reported that the ingestion of apple juice (AJ) markedly reduced the plasma concentration of atenolol; however, our in vitro study showed that atenolol may not be a substrate of organic anion transporting polypeptide 2B1 (OATP2B1), so this AJ-atenolol interaction cannot be explained by inhibition of OATP2B1. On the other hand, we more recently showed that the solution osmolality influences gastrointestinal (GI) water volume, and this may indirectly affect intestinal drug absorption. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…It is interesting that rOATP1A5 and human OCT1 are inhibited by fruit juice flavonoids (Dresser et al, 2002;Mimura et al, 2015). The possibility remains that alterations in intestinal water movement caused by the high osmolarities of the AJ and GFJ vehicles used in this study (2794 and 2464 mOsm/kg, respectively) have affected fexofenadine absorption in a similar fashion as was observed for the atenolol-AJ interaction in rats (Funai et al, 2019).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is interesting that rOATP1A5 and human OCT1 are inhibited by fruit juice flavonoids (Dresser et al, 2002;Mimura et al, 2015). The possibility remains that alterations in intestinal water movement caused by the high osmolarities of the AJ and GFJ vehicles used in this study (2794 and 2464 mOsm/kg, respectively) have affected fexofenadine absorption in a similar fashion as was observed for the atenolol-AJ interaction in rats (Funai et al, 2019).…”
Section: Discussionsupporting
confidence: 52%
“…For instance, there are some poorly metabolized OATP2B1 substrates such as rosuvastatin and pravastatin that are not subject to significantly reduced oral absorption when taken together with fruit juices in clinical studies (Lilja et al, 1999;Kashihara et al, 2017). Additionally, a recent study showed that the major clinical drug interaction between atenolol and apple juice is not related to OATP2B1 since the drug is not a substrate and osmolarity may be a contributing factor (Funai et al, 2019). Another potentially disconcerting observation are reports that show that OATP2B1 is localized to the basolateral (Mooij et al, 2016;Keiser et al, 2017) rather than the apical (luminal) membrane of enterocytes (Kobayashi et al, 2003), casting doubt on a role in oral drug absorption and fooddrug interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Solution osmolality influences gut‐lumen fluid volume, which then alters drug concentration and impacts absorption by decreasing the concentration gradient, especially for low‐permeability compounds 59 . For example, administering atenolol with apple juice (∼750 mOsm/kg) results in a 63% decrease in bioavailability compared with administering the drug with purified water 59 . This may, in part, be a function of apple juice's ability to inhibit a specific transporter involved in atenolol absorption 54…”
Section: Influence Of Nutrition Interactionsmentioning
confidence: 99%
“…Aside from pharmacokinetic interactions at transporters/enzymes caused by food components, the characteristics of fluid intake may alter drug bioavailability. Solution osmolality influences gut‐lumen fluid volume, which then alters drug concentration and impacts absorption by decreasing the concentration gradient, especially for low‐permeability compounds 59 . For example, administering atenolol with apple juice (∼750 mOsm/kg) results in a 63% decrease in bioavailability compared with administering the drug with purified water 59 .…”
Section: Influence Of Nutrition Interactionsmentioning
confidence: 99%
“…Specifically, the fraction absorbed of atenolol (a low-permeability drug) was significantly greater when administered in purified water than when administered in isosmotic solution, while there was no significant difference in the fraction absorbed of antipyrine (a high-permeability drug). We also showed that the high-osmolality environment in the GI tract resulting from oral ingestion of apple juice induces secretion of water into the lumen, resulting in a reduction of luminal concentration and decreased absorption of coadministered atenolol [ 2 ].…”
Section: Introductionmentioning
confidence: 99%